2018
DOI: 10.7883/yoken.jjid.2017.585
|View full text |Cite
|
Sign up to set email alerts
|

Two Neuropsychiatric Cases Seropositive for Bornavirus Improved by Ribavirin

Abstract: A c c e p t e d M a n u s c r i p t While we had previously detected anti-bornavirus antibodies via radioligand assay in psychiatric patients, we had not examined the viral pathogenicity in these individuals.Herein, we present two psychiatric patients who were seropositive for bornavirus and whose treatment-resistant symptoms improved by oral administration of ribavirin, a broad-spectrum antiviral agent. Cerebrospinal fluid analysis indicated that the ribavirin affected the central nervous system of these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The specific serum antibody levels at the end of the ribavirin administration were similar to those before treatment. However, in one previously reported case that was responsive to ribavirin, a decrease in antibody levels was observed 2 years after the end of treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific serum antibody levels at the end of the ribavirin administration were similar to those before treatment. However, in one previously reported case that was responsive to ribavirin, a decrease in antibody levels was observed 2 years after the end of treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although hemolytic anemia is a common side effect of ribavirin treatment and caution should be exercised given the risk of teratogenicity, it is unlikely to cause any other serious side effects. A previously reported clinical trial of oral ribavirin in seropositive patients with refractory neuropsychiatric symptoms showed clear improvement in two of nine patients [ 23 ]. Here, we report the case of a patient with a medical history of severe schizophrenia for more than 30 years who showed some improvement after ribavirin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although it is still controversial, several studies have reported potential human cases of bornavirus infection in various psychiatric disorders (Nakamura et al, 2000; Honda et al, 2017b, 2018). Indeed, there are a few human case reports showing remission of symptoms after treatment with antivirals against bornaviruses, although the causative relationship is unclear (Matsunaga et al, 2018). So far, ribavirin and T-705 (favipiravir) are nominated as antivirals against bornaviruses (Mizutani et al, 1998; Musser et al, 2015; Reuter et al, 2016; Tokunaga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%